T1 Radiculopathy: Electrodiagnostic Evaluation - Radecki, Jeffrey (Springer-Verlag, 2008)
Electromyography (EMG) studies are useful in the anatomical localization of nerve injuries and, in most cases, isolating lesions to a single nerve root level. Their utility is important in identifying specific nerve-root-level injuries where surgical or interventional procedures may be warranted. In this case report, an individual presented with right upper extremity radicular symptoms consistent with a clinical diagnosis of cervical radiculopathy. EMG studies revealed that the lesion could be more specifically isolated to the T1 nerve root and, furthermore, provided evidence that the abductor pollicis brevis receives predominantly T1 innervation.